Plan de acción de mejora para la línea de porcionado en la empresa Frigociam S.A con base sistema HACCP - Andrea Carolina Rodríguez Silva, Víctor Hugo Trujillo Alarcón (Universidad Antonio Nariño, 2021)
Currently there is concern about the loss of safety that occurs in the processing of beef; this study proposes a design of the Hazard Analysis and Critical Control Point (HACCP) system aimed at improving and strengthening the safety of the beef portioning line in the company FRIGOCIAM S. A. This research was carried out through the hazard analysis and identification of critical control points (CCP), the establishment of critical limits, corrective actions and the establishment of documentation and verification procedures. A. This research was carried out through hazard analysis and the identification of critical control points (CCP), the establishment of critical limits, corrective actions and the establishment of documentation and verification procedures. Information gathering methods were used for this approach, such as interviews and guided tours of the production plant, the use of field diaries to analyze the flow of processes and an evaluation of compliance with infrastructure conditions and prerequisite plans as established in regulations such as Decree 1500 of 2007, Decree 060 of 2002 and Resolution 240 of 2013. Similarly, analysis tools such as a checklist, a decision tree and some matrices were used, where important aspects that ratify the research problem were identified, such as the lack of a Safety Assurance System; whose design and approach contributed to the objective of making an improvement plan to ensure the safety of the products of FRIGOCIAM S.A. company.